Primary CNS lymphoma in a patient treated with azathioprine. (1st September 2014) - Glesner, Matilde Kanstrup; Ocias, Lukas Frans; Larsen, Thomas Stauffer; Pedersen, Court
Abstract : A 33-year-old man treated with azathioprine for 12 years for Crohn's disease presented with headache, nausea and vomiting accompanied by difficulty in putting words together and slight mental confusion. Prednisolone and antibiotics were without effect. MRI of the brain showed multiple focal lesions with surrounding oedema. There was cerebrospinal fluid pleocytosis, and Epstein-Barr virus (EBV) DNA was detected in the spinal fluid by PCR. A brain biopsy confirmed the suspicion of primary brain lymphoma. EBV-associated primary brain lymphoma is a relevant differential diagnosis in patients with long-standing immune suppression presenting with neurological symptoms. Detection of EBV DNA in the spinal fluid together with characteristic radiological findings may serve as a diagnostic clue for a quick diagnosis.